A Case of Influenza A (H3N2) Complicated by Community-Acquired Pneumonia and Death in a Young Healthy Adult during the 2013–2014 Season - Collins, Lauren F.; Anderson, Benjamin D.; Gray, Gregory C. (Frontiers in Public Health, 2017)
With multiple available vaccines and antivirals, seasonal influenza A is typically a self-limited acutely debilitating illness in young healthy adults. Here we illustrate unexpected morbidity and mortality in a relatively young and healthy patient seen at a large tertiary care academic medical center for seasonal influenza A (H3N2) complicated by community-acquired pneumonia, hypoxic respiratory failure, septic shock and death.